IMPLEMENTASI PELAYANAN SAMSAT CORNER DALAM RANGKA MENINGKATKAN PELAYANAN PAJAK KENDARAAN BERMOTOR (Studi Pada Samsat Corner Galeria Mall Yogyakarta) - Amri, Pahmi (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
Along with the issuance of the Joint Regulation of Governor of Yogyakarta Special Region, Regional Police Chief of Yogyakarta Special Region, and Operational Director of PT. Jasa Raharja No.35 Year 2008 No:B/4820/XI/2008 and No: SKEB/12/2008 about the program to improve SAMSAT’s excellent service, SAMSAT Corner was established. Vehicle tax is one of tax incomes which affects regional income. Therefore, it is necessary to optimize the tax revenue of vehicle through various efforts. One of the ways is by improving the satisfaction of vehicle taxpayers by giving an optimal service quality. Based on the explanation above, the researcher was eager to find out the implementation of SAMSAT Corner service at Galleria Mall in order to improve vehicle tax in 2014.Based on the analysis, it can be concluded that the implementation of SAMSAT Corner service at Galleria Mall has run well and it gives positive effects to society (vehicle taxpayers).However, the regulation that rules the operation of SAMSAT Corner service at Galleria Mallis not optimal yet, so it is necessary to study it again in order to have a clear regulation about SAMSAT Corner service.